Manajemen Evaluasi Diri dalam Menyusun Anggaran Menggunakan Aplikasi EDM e-RKAM pada Madrasah Sasaran Proyek (REP-MEQR) - Muhtasar Muhtasar; Fahrurrozi Fahrurrozi; Lukman Hakim (MANAZHIM, 2023)
The EDM - e-RKAM application opens opportunities for the management of BOS funds and other funds in a more transparent and accountable manner, which can be accessed in stages starting at the madrasah level, Regency/City Ministry of Religion Offices, Regional Offices of the Provincial Ministry of Religion to the level of the Indonesian Ministry of Religion. The use of the e-RKAM and EDM applications is expected to cut reporting bureaucracy. This digital transformation is a concrete effort to realize more effective, efficient, transparent and corruption-free management of the education budget. The objectives in this study are: Knowing the Implementation of Self-Evaluation management in compiling using the EDM e-RKAM Application. Application. This research is a qualitative research with a descriptive research method that was conducted with the aim of describing or describing the implementation of self-evaluation management, supporting and inhibiting factors and strategies for overcoming obstacles to the implementation of Evaluation management. Madrasah Self-Evaluation Management went through 4 stages, namely the formation of the Madrasah Development Team filling in the Self-Evaluation Instruments Madrasah, presentation of the work of the Madrasah Development Team and conclusion of the presentation of the Madrasah Development Team